Reassessing Twenty Years of Vaccine Development Against Tuberculosis - Stefan H. Kaufmann (Frontiers Research Topics, 2018)
Tuberculosis (TB) remains the prime bacterial infection worldwide with 10.4 million infections and a death toll of 1.7 million people in 2016 according to WHO statistics. Tuberculosis is caused by members of the Mycobacterium tuberculosis complex, facultative intracellular bacteria able to thrive within otherwise potent innate defense cells, the macrophages. In a world of increasing numbers of infections with drug resistant M. tuberculosis strains, the daunting race between developing new therapeutics and emerging resistant strains will hardly produce a winner. This cycle can only be broken by enhancing population wide immune control through a better vaccine as the only one currently in use, M. bovis Bacillus Calmette Guerin (BCG). The protective efficacy of BCG against pulmonary tuberculosis in all age groups is dissatisfying and geographically highly diverse with the tropical areas showing the lowest efficacy rates. Despite worldwide vaccination coverage, the impact of BCG on the steep decrease of tuberculosis incidence rates in the developed world seems therefore questionable and can rather be attributed to improved social, housing and nutritional conditions, better health care, surveillance and treatment systems. The last 15 years saw tremendous efforts to improve vaccination strategies against tuberculosis. Different paths of vaccine approaches were followed including genetically improved BCG strains, attenuated M. tuberculosis variants, recombinant viral vectors and subunit vaccine candidates combined with novel more potent adjuvants. With the first novel vaccine candidates being evaluated in clinical phases II and III and initial results chastening the expectations, a critical reassessment of all candidates is inevitable. Here, we assembled experts to review and assess the current status of novel anti-tuberculosis vaccine candidates, their efficacy and prospects for implementation as well as the pitfalls and possible measures for improvement.